IMPLEMENTASI METODE PIECES FRAMEWORK PADA TINGKAT KEPUASAN PENGGUNAAN APLIKASI MYPSB MEJASEM - Faqih, Husni; Rousyati, Rousyati; Mubarok, Husni; Pangestu, Andika Tulus; Akbar, Muhammad Taufan (Jurnal Teknoinfo, 2024)
The need for digitizing schools is currently quite massive due to calls from the central and regional governments. In addition, the development of digital technology has changed the behavior of people who rely more on digital technology so that it is easy and fast to do their activities. One form of school digitization on the school management side is online acceptance of new students. The MyPSB Mejasem application is an online new student admissions information system that is used by SDN Mejasem Barat 01. To improve the service quality of this application, an evaluation is needed regarding user satisfaction with the MyPSB Mejasem application. The PIECES Framework method, which is a framework for classifying a problem, opportunity, and direction in the scope of information system analysis, is the analytical method used because it can provide real results on the effectiveness of the system used. This method has six indicators in its analysis such as Performance, Information, Economics, Control and Security, Efficiency and Service. From measurements with the PIECES Framework, the average value of the six indicators is 4.30, which is a very good value with satisfactory category results according to the characteristics of the Rikert scale assessor.